Living With Less for a Better Planet: Empirical Insights into Minimalism, TPB Constructs, Collectivist Culture and Sustainable Consumption Behaviours - Boadziwa Sackey, Baaba; Jingzhao, Yang; Kwasi Sampene, Agyemang; Boadu, Bright (Journal of Tourism and Services, 2025)
Amid escalating environmental challenges and shifting consumer values, understanding the psychological and cultural drivers of sustainable consumption has become imperative. This study examines the impact of minimalism on sustainable consumption behaviors among Generation Z consumers in China, utilizing the Theory of Planned Behavior (TPB) constructs: attitude towards behavior, perceived behavioral control, and perceived social expectations as driving mechanisms. However, a clear research gap exists in understanding how minimalism, as a lifestyle orientation, interacts with cultural values such as collectivism to shape sustainable consumption behaviors among Generation Z consumers. Motivated by the underexplored role of minimalism in shaping pro-environmental choices, the study further examines the moderating effect of collectivist culture on these relationships. A cross-sectional survey design was employed, and data were collected from 455 respondents using systematic random sampling in the Province, China. The Partial Least Squares Structural Equation Modelling (PLS-SEM) technique was employed to test the hypothesized relationships. The findings reveal that minimalism has a significant and positive influence on sustainable consumption behaviors. In addition, the TPB construct, comprising attitude towards behaviour, perceived behavioural control, and perceived social expectations, significantly influences sustainable consumption behaviours. Additionally, collectivist cultural orientation was found to strengthen the impact of minimalism on sustainable consumption behaviours. The study is unique in integrating minimalism and collectivist culture within the TPB framework, offering novel insights applicable to the tourism and services sectors, where sustainable consumption choices are increasingly vital. Policy implications underscore the need for culturally grounded sustainability campaigns, minimalist education in youth-targeted programs, and supportive infrastructure to encourage low-consumption lifestyles. The study offers a novel and empirically grounded contribution to sustainable consumer behaviour literature and serves as a benchmark for future cross-cultural and longitudinal research.